Enhancing Zakat Collection Agency (BAZNAS) Performance through Good Corporate Governance Principles: An Institutional Economics Approach - Erwin, Erwin (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the application of good corporate governance (GCG) principles in improving the performance of BAZNAS Palopo City; the obstacles and challenges faced in implementing the principles of good corporate governance (GCG); and the application of good corporate governance (GCG) principles in improving BAZNAS performance using an institutional economic approach. The research method used is descriptive qualitative with data collection through in-depth interviews with research informants. Analysis can be done through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of GCG has been carried out optimally in increasing transparency, accountability, and effectiveness of zakat management. However, there are still several aspects of GCG that need to be improved to achieve optimal performance; the obstacles faced are superior management or leaders and the quality of human resources (HR) which are still limited. Furthermore, this study also shows that the application of GCG principles with an institutional economic approach can be done through continuous interaction with all stakeholders and innovation and adaptation through the use of digital platforms. This study offers a new policy for BAZNAS management with an institutional economic approach that is still rarely explored in previous research.